The effects of ginger (Zingiber officinale) rhizome extract on ethanol-induced behaviors in C. elegans - Rafael Vincent Mercado Manalo , Bianca Louise C. Lapuz, Krisha K. Lim, Katelyn Edelwina Y. Legaspi, Patricia Marie M. Lota, Francine Melissa B. Lucas, Abdelaziz N. Maldisa, Vinson C. Malipot, Christine Bernadette O. Lo, Allen Khriztofer P. Lichauco, Paul Mark Baco Medina (Journal of Applied Pharmaceutical Science, 2022)
Ginger has been used traditionally as a hangover cure in Asia, with potential GABAergic and anti-withdrawal properties. However, studies on its use remain scarce, despite the increasing prevalence of alcohol disorders. Hence, we sought to determine the effects of ginger (Zingiber officinale) rhizome extract (GRE) on alcohol-induced behaviors in Caenorhabditis elegans. Nematodes were exposed to either vehicle (KPO4 ) or ethanol (EtOH) ± GRE at 10-fold dilutions (1, 10, 100, 500, and 1,000 µg/ml) and were tested for acute depression and tolerance, withdrawal, and associative learning. We found that GRE at 500 and 1,000 µg/ml acted as an acute depressant of reversals, omega turns, and sensations to light and nose touches. Interestingly, GRE at the same concentrations also increased the recovery of nematodes at 40 minutes, suggesting an improvement in tolerance. GRE was also able to reduce withdrawal-induced deficits in locomotion and decreased learned preference to EtOH by 53% at 1,000 µg/ml. Altogether, these data show that GRE is a short-acting depressant that improves tolerance, tapers withdrawal-induced behavioral deficits, and disrupts learned preference to EtOH in C. elegans.
Keywords: Alcohol, addiction, tolerance, withdrawal, C. elegans